2007
DOI: 10.1093/jn/137.4.930
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Total, Dairy, and Meat Protein with Markers for Bone Turnover in Healthy, Prepubertal Boys

Abstract: We previously reported that high intake of milk, but not meat, equal in protein content, increased serum insulin-like growth factor-I (sIGF-I) in prepubertal boys. sIGF-I plays a key role in bone metabolism. Therefore, the aim of this cross-sectional study was to investigate associations of total, dairy, and meat protein intake with markers for bone turnover and sIGF-I in prepubertal, healthy boys (n = 81). We measured bone turnover (enzyme-linked immunoassay) in serum osteocalcin (sOC), bone-specific alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
3
24
1
1
Order By: Relevance
“…This study highlighted that a significant correlation between IGF-IZ and energy or protein intake was found only in 9 to 11-year-old males for energy intake and in 7 to 9-year-old females for energy and protein intakes immediately before their adolescence or the onset of puberty. There were two major differences between this study and previous studies that have targeted healthy children (Hoppe et al, 2004;Budek et al, 2007;Kerver et al, 2010). First, previous studies reported the relevance of animal protein intake to IGF-I level; in contrast, this study found the relevance of protein and energy intakes.…”
Section: Effects Of Disease and Hormonal Status On Growthcontrasting
confidence: 69%
See 2 more Smart Citations
“…This study highlighted that a significant correlation between IGF-IZ and energy or protein intake was found only in 9 to 11-year-old males for energy intake and in 7 to 9-year-old females for energy and protein intakes immediately before their adolescence or the onset of puberty. There were two major differences between this study and previous studies that have targeted healthy children (Hoppe et al, 2004;Budek et al, 2007;Kerver et al, 2010). First, previous studies reported the relevance of animal protein intake to IGF-I level; in contrast, this study found the relevance of protein and energy intakes.…”
Section: Effects Of Disease and Hormonal Status On Growthcontrasting
confidence: 69%
“…Malnutrition and a high burden of infectious diseases are involved in delaying the onset of puberty, although elucidation of the underlying physiological mechanisms through which this delay occurs has remained elusive (McDade, 2003). The determining role of nutrient intake in IGF-I level has been recognized not only among malnourished children (Nazaimoon et al, 1996;Mart ınez de Icaya et al, 2000) and children with anorexia nervosa (Misra et al, 2004) but also among healthy children (Hoppe et al, 2004;Budek et al, 2007;Kerver et al, 2010). Therefore, it is possible that the correlation between nutritional status and nutrient intake is mediated by IGF-I.…”
Section: Effects Of Disease and Hormonal Status On Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Some, but not all (22), studies have found that meat as a protein source is associated with higher serum levels of IGF-1 (20,21), which is in turn associated with increased bone mineralization and fewer fractures (23). Soy foods have been linked with lower levels of IGF-1 (21).…”
Section: Protein Sourcementioning
confidence: 99%
“…Dietary protein also increases IGF-I levels during growth, as milk supplementation increased serum IGF-I levels in adolescent girls (Cadogan et al, 1997). Serum IGF-I was positively associated with dietary protein in 8-year-old boys (Budek et al, 2007). Historically, dietary protein was thought to have a negative effect on Ca balance and bone mass.…”
Section: Dietary Protein Modulating Igf-1mentioning
confidence: 99%